Individual credit ranking by an integrated interval type-2 trapezoidal fuzzy Electre methodology - Ayyildiz, Ertugrul; Taskin Gumus, Alev; Erkan, Merve (SPRINGER, 2020)
In this paper, first, it is aimed to determine the most important criteria which affect the credit evaluation process. A type-2 trapezoidal fuzzy analytic hierarchy process method is proposed to analyze the criteria influencing the credit evaluation. Then, a ranking of experts is obtained using a type-2 trapezoidal fuzzy Electre (elimination and choice translating reality English) method. Lastly, the applicants' ranking is determined as a real case. This method is aimed to be used by public and private banks to improve their credit ranking and evaluation strategies. Finally, the applicability and feasibility of the proposed approach are demonstrated by providing the results and sensitivity analysis.
Keywords: Credit ranking model; Electre; AHP; Interval type-2 trapezoidal fuzzy numbers; ANALYTIC HIERARCHY PROCESS; DECISION-MAKING; TOPSIS METHOD; FIRMS; TECHNOLOGY; QUALITY; DELPHI; MODEL; Computer Science